Sistim Dan Prosedur Pelatihan Dan Pengembangan Terhadap Kinerja Karyawan BCA - Ria Anggelina; Oey Hannes Widjaya (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
Employee performance in banking activities plays an important role in maintaining the presence of the Bank's customers. At BCA there are problems between the services provided Employees often do not satisfy the customers as the service is slow, difficult to conduct transactions. The research sample used was non-probability sampling with a sample of 100 employees in PT.BCA. Data analysis techniques used are validity and reliability, test classic assumptions and hypotheses. The results showed that there are significant systems and procedures for employee training and the development of the quality of employee performance at PT. BCA with a 95% confidence level.